2010
DOI: 10.1016/j.biopsych.2009.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Produces a Behavioral Phenotype Mediated by Low Cyclic Adenosine Monophosphate Response Element Binding (CREB) Activity in the Nucleus Accumbens

Abstract: Background-Previous research has shown that rats reared in an enriched condition (EC) are more sensitive to the acute effects of amphetamine than rats reared in an isolated condition (IC); yet, EC rats self-administer less amphetamine than IC rats. The present study used cocaine to further explore this environmental enrichment behavioral phenotype, as well as the underlying molecular mechanisms involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
176
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(217 citation statements)
references
References 27 publications
28
176
4
3
Order By: Relevance
“…The relationship of signaling pathways secondary to growth factors with depression-and anxiety-like behavior is another focus of interest. For instance a study has reported that the expression of the active (phosphorylated) form of cyclic adenosine monophosphate (cAMP) response element binding protein (CREB) in the NAc was decreased following EE (45). In parallel with this finding, knockdown of CREB in the NAc resulted in decreased depression-like and increased anxiety-like behavior similar to that caused by EE.…”
Section: Alexander Et Al (2010) Investigated the Effect Of P11supporting
confidence: 53%
“…The relationship of signaling pathways secondary to growth factors with depression-and anxiety-like behavior is another focus of interest. For instance a study has reported that the expression of the active (phosphorylated) form of cyclic adenosine monophosphate (cAMP) response element binding protein (CREB) in the NAc was decreased following EE (45). In parallel with this finding, knockdown of CREB in the NAc resulted in decreased depression-like and increased anxiety-like behavior similar to that caused by EE.…”
Section: Alexander Et Al (2010) Investigated the Effect Of P11supporting
confidence: 53%
“…Similar to enhanced sensitization to repeated stimulants, IC rats show greater propensity to selfadminister amphetamine and cocaine relative to EC rats (Bardo et al, 2001;Miczek et al, 2008;Green et al, 2010;Gipson et al, 2011a). This difference is greater at low unit doses than at high unit doses delivered on either FR or PR schedules.…”
Section: B Social Influencesmentioning
confidence: 95%
“…We used three tests of anxiety-like behavior; the elevated plus-maze (EPM), cold stress defecation, and neophobia to a novel taste (sucrose) (6,16). At the beginning of the EPM test, the rat was placed in the central area facing one of the open arms.…”
Section: Animals and Induction Of Ulcerative Colitis-like Inflammationmentioning
confidence: 99%
“…We employed three tests to model distinct aspects of depression-like behavior: the sucrose preference test to model anhedonia, the social interaction test to model social withdrawal, and the forced swim test to model behavioral despair (16). In the sucrose preference test, rats were preexposed to 1% (wt./vol.)…”
Section: Animals and Induction Of Ulcerative Colitis-like Inflammationmentioning
confidence: 99%
See 1 more Smart Citation